Relationship between repetitive behaviour and fear across normative development, autism spectrum disorder, and down syndrome. Issue 3 (26th July 2016) - Uljarević, Mirko; Evans, David W.
Abstract : The present study had two aims: first to compare levels of restricted and repetitive behaviours (RRB) across two groups of typically developing (TD) children, and two disorders: Autism Spectrum Disorder (ASD) and Down syndrome (DS), and second to explore the relationship between fear and repetitive behaviours in these four groups. Parents of 41 offspring with ASD ( M age = 123.39 months, SDage = 27.67), 38 offspring with DS ( M age = 125.37 months, SDage = 45.71), 45 typically developing children matched to the mental age (MA) of the DS group (TD MA; M age = 51.13 months, SDage = 22.1), and 42 chronological age (TD CA; M age = 117.93 months, SDage = 22.91) matched TD children, completed measures of RRB and fear. ANOVAs revealed differences across the four groups on the RRB subscale scores: "Just Right" F (3, 162) = 16.62, P < 0.001; Rigid Routines F (3, 162) = 52.76, P < 0.001; Sensory behaviours F (3, 162) = 23.26, P < 0.001. Post‐hoc comparisons revealed that children with ASD had the highest RRB levels followed by DS, TD MA, and TD CA children. In children with ASD, higher levels of fear were related to higher RRB levels. Similar, albeit less strong, patterns of associations was found among DS and TD MA children but not in older TD CA children. This study provided evidence of a fear‐RRB association in children with ASD, DS, and two groups of TD children. Autism Res 2017, 10: 502–507 . © 2016 International Society for Autism Research, Wiley Periodicals, Inc.